(untitled) (Damu Journal of Sport Sciences, 2024)
The aim of the research was to develop an educational curriculum using two methods (command and training) in teaching some table tennis skills and developing learning motivation for intermediate school students. It also aimed to identify the impact of this method on the research sample and the optimal method used in learning the forehand and backhand skills. The researcher hypothesized that there would be statistically significant differences in the use of the command and training methods for the pre- and post-tests of the research sample, in favor of the post-test. The researcher used an experimental method with two groups, one experimental and the other a control group, with 30 students per group from Al-Rawad and Al-Shahid Abu Al-Maali intermediate schools in Karbala Education for the academic year. 2021/2022, with a total number of (60) students. The researcher concluded that the command method and the training method have a positive impact on learning the skills of the forehand and backhand stroke and developing learning motivation, and that the training method is more appropriate for learning the backhand stroke skill, while learning the forehand stroke is more suitable for the command method. The researcher recommended the need to conduct similar studies on other activities using these teaching methods that rely on modern education and achieve educational and pedagogical goals.